Peningkatan Literasi Finansial dan Digitalisasi Pemasaran pada Kelompok Tani Hutan Green Lawu Kabupaten Karanganyar: Improving Financial Literacy and Marketing Digitalization in the Green Lawu Forest Farmers Group, Karanganyar Regency - Khairiyakh, Refa'ul; Nurhidayati, Indah; Sutrisno, Joko; Irawan, Evi; Ulfa, Amalia Nadifta; Agustono, Agustono; Fajarningsih, Rhina Uchyani (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The Green Lawu Forest Farmers Group (KTH) is located in Berjo Village, Ngargoyoso District, Karanganyar Regency. KTH Green Lawu is a group whose members live in the area around the Mangkunagoro I Karanganyar Grand Forest Park. This group cultivates and sells orchids to improve the economy of its members. However, the activities of KTH Green Lawu still face various obstacles in its development, including the low knowledge of members regarding financial management, and not yet having the capacity to expand the market. The community service activity carried out by the RG Natural Resources Economics UNS, namely "Training to Improve Financial Literacy and Digitalization of Marketing in the Green Lawu Forest Farmers Group (KTH) Karanganyar Regency", is expected to be able to overcome these problems. This activity was carried out on June 8, 2024, where previously the community service team had carried out initial coordination with partners and technical preparation for the service. The materials provided in this activity were financial bookkeeping and online marketing. The community service activities that have been carried out are expected to be able to increase the capacity of KTH Green Lawu members regarding financial administration and online marketing so that in the future KTH Green Lawu can become more advanced.